Detection of Crispr-Cas9 Mutations Using a Carbon Nanotube-Modified Electrochemical Genosensor - Kıvrak, Ezgi; Yılmaz, Selahattin; Pauzaite, Tekle; Copeland, Nikki A.; Hardy, John G.; Kara, Pınar; Fırlak, Melike; İnce Yardımcı, Atike; Yılmaz, Selahattin; Palaz, Fahreddin (MDPI, 2021)
The CRISPR-Cas9 system has facilitated the genetic modification of various model organisms and cell lines. The outcomes of any CRISPR-Cas9 assay should be investigated to ensure/improve the precision of genome engineering. In this study, carbon nanotube-modified disposable pencil graphite electrodes (CNT/PGEs) were used to develop a label-free electrochemical nanogenosensor for the detection of point mutations generated in the genome by using the CRISPR-Cas9 system. Carbodiimide chemistry was used to immobilize the 5 '-aminohexyl-linked inosine-substituted probe on the surface of the sensor. After hybridization between the target sequence and probe at the sensor surface, guanine oxidation signals were monitored using differential pulse voltammetry (DPV). Optimization of the sensitivity of the nanogenoassay resulted in a lower detection limit of 213.7 nM. The nanogenosensor was highly specific for the detection of the precisely edited DNA sequence. This method allows for a rapid and easy investigation of the products of CRISPR-based gene editing and can be further developed to an array system for multiplex detection of different-gene editing outcomes.
Keywords: CRISPR-Cas9; Homology-directed repair (HDR); Electrochemical genosensor; Mutation detection; Carbon nanotube-modified PGE